พฤติกรรมการเปิดรับและการรับรู้ข่าวสารบนเฟซบุ๊กข่าวสด ของประชากรในกรุงเทพมหานคร - ชมบริสุทธิ์, ณัฏญา (Journal of Graduate School Sakon Nakhon Rajabhat University, 2019)
The purpose of this research was to study the exposure and perception of news on Facebook of the population in Bangkok. This research is a qualitative research and key informants used in the study were 6 groups, are the follower of Facebook news of Generation X, Generation Y and Generation Z, there are both female and male. The research found that followers news on Facebook, there are both female and male of Generation X have open crime on 8.00 am. about 30 minutes and 2-3 times a day to get news to get to know the news event each day. Female of Generation Y have open for entertainment news, from 6.00 am to 7.00 pm, about 15 minutes, 5 times a day for newsletters and bring the news to close friends. Male of Generation Y have open for sport news, on 8.00 pm, about 15 minutes, 5 times a day for got newsletters for information to be exposed to the current situation in society. Female of Generation Z have open for entertainment news and Male of Generation Z have open for technology news, on 5 pm., about 10 minutes, 1 times a day for newsletters and bring the news for use in education. Keywords : Behavior, Khaosod, Facebook, Generation X, Generation Y, Generation Z